A reliable framework for supply chain management using cluster based blockchain for intelligent industrial automation - Alsolami, Eesa; Al-khasawenh, Mahmoud Ahmad; Alarood, Ala Abdulsalam; Alzahrani, Ahmed Omar; Ibraheem, Ahmed Aalameen; Zamani, Mazdak (Scientific reports, 2025)
Industrial automation is an integral part of Industry 4.0, and this scenario needs intelligent mechanisms to improve the industry’s production level. Manufacturing industries depend entirely on supply chain management to track the entire system’s performance, which will be the key term to improving product quality. In the modern era of industrial automation, technology entirely depends on intelligent computing algorithms. This paper proposes a reliable framework for supply chain management using cluster-based blockchain technology. The proposed method contains two main contributions. The first is to maintain the information organized using Blockchain Technology, and the second is to analyze the Blockchain by extracting valuable information to make an intelligent system in industrial automation. The proposed framework’s performance evaluation is based on execution time cost analysis for Blockchain, accuracy, and mean error value analysis for the cluster-based project key factors classification. Software Development applications with 26 software metrics are used for the performance evaluation. The performance analysis for the proposed framework archives 93% for software development project clustering concerning the evaluation dataset. The result shows that the optimum average size of cluster selection will produce a high accuracy of the suitable Blockchain for the new project.